Chapter Tuna: underwater natural and cultural heritage. The Tunèa case study, a project for the re- connection between coastal community and marine ecosystem - Usai, Maria Pina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Understanding the intersection between marine nature and culture is a basis for sustainable coastal development. In this frame the Carloforte tonnara, one of the last fixed Thunnus thynnus trap in the Mediterranean, represent a significant case study. Since until about thirty years ago the life of local community was closely linked to the fishing activities, but the evolution of the fish market at a global scale has radically interrupted it. In 2021 the author of this contribution created Tunèa1, an arts-based research in action project, aimed to re-create the lost relationship in new forms.